MODEL PENYELESAIAN KONFLIK ANTAR KELOMPOK DENGAN PENDEKATAN MAHFUDZAT - Muthoifin -; Nuha - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Admittedly, though famous for its tolerant Islam Indonesia, moderate, fair and mid will remain in Indonesia are still vulnerable happened assorted conflicts. In fact this is already happening almost at various places. Ranging from religious conflicts, ethnic, racial, and other groups. This is because each party could not keep away from lust, egoism, fanaticism and loss of consciousness. Most do not have occurred at least five cases of the worst conflicts in the archipelago, such as the conflict between Muslims and Christians in Maluku, Dayak and Madurese ethnic conflict in Sampit and Sambas, violence etinis Chinese in Jakarta, slaughter Ahmadiyah group in Mataram, as well as the massacre of Hindu groups in Lampung. Not to Mention the small conflicts in various regions, such as the conflict between the followers MTA NU activists in Central Java, Sunni with Shia conflict in Madura, and various other conflicts. The focus of the research is to reveal the various conflicts in Indonesia and solutions overcome in order to create harmony and peace betwen groups in a review of mahfudzat. Results of the study were, the teachings of Islam and mahfudzat in Indonesia it can be used as an answer to unravel various conflicts, discrimination, and other controversies. Among mahfudzat texts and teaching of islam are always invite someone to respect, both to themselves and to others, must be able to withstand egoism and avoid fanaticism group, moderate in hating and loving, self reformation, along well, preaching with wisdom, seat people according to the level and ability, do our best and useful.Keywords: Conflict, Peace, Perspective, Mahfudzat.